HARMONI SOSIAL DI TENGAH PLURALITAS BERBANGSA DAN BERNEGARA - I Ketut Widnya (Purwadita : Jurnal Agama dan Budaya, 2019)
In the history of multiculture in Indonesia, religion as the main multicultural formation,has never been the main factor that caused the conflict. Both before independence, such as theShiva Buddhist period, and after independence. From our historical perspective there are actuallymany data that reveal social harmony rather than conflicts that occur in a multicultural society.Lately, politics has always brought religion. On the one hand, politics commits violence in thename of religion. On the other hand, it is strongly criticized in the name of religion. In bothcases there is a hidden politics that sells religion at cheap prices. Finally, religion got its sap asa trigger for conflict. In fact, religion has become social cohesion among multiculturalcommunities. The emergence of radicalism and terrorism in Indonesia has become the biggestthreat to multicultural development in Indonesia. Even within the country, Indonesia is actuallya producer of radicalism and terrorism, so it does not need to infiltrate from abroad. As a result,the task of realizing social harmony will be heavier with the presence of radicalism and terrorismin the country.